Assessment of the anti-biofilm effect of micafungin in an animal model of catheter-related candidemia. (12th September 2018) - Salinas, Beatriz; Guembe, María; Cussó, Lorena; Kestler, Martha; Guinea, Jesús; Desco, Manuel; Muñoz, Patricia; Bouza, Emilio
Abstract: In cases where catheter-related candidemia (CRC) must be managed without catheter withdrawal, antifungal lock therapy using highly active anti-biofilm (HAAB) agents is combined with systemic treatment. However, the activity of HAAB agents has never been studied in in vivo models using bioluminescence. We assessed the efficacy of micafungin using a bioluminescent Candida albicans SKCA23-ACTgLuc strain in an animal model of CRC. We divided 33 female Wistar rats into five groups: sham (A), infected nontreated (B), treated with lock therapy (0.16 mg/ml) (C), systemically treated only (1 mg/kg) (D), and systemically treated+lock (E). Catheters were colonized 24 h before insertion into the femoral vein (day 0). Treatment started on day 1 and lasted 7 days, followed by 7 days of surveillance. Bioluminescence assays were carried out on days 1, 3, 5, and 14, together with daily monitoring of clinical variables. Postmortem microbiological cultures from the catheter and several tissue samples were also obtained. Overall, 28 rats (84.8%) completed the study. Group B animals showed significant weight loss at days 2, 4, and 5 compared with groups C and D ( P < .05). In group B, no animals survived after day 7, 75% had CRC, and bioluminescence remained constant 5 days after catheter implantation. Positive catheter culture rates in groups C, D, and E were, respectively, 83.3%, 62.5%, and 25.0% ( P = .15). Micafungin proved to be a HAAB agent when administered both systemically and in lock therapy in an animal model of CRC, although the bioluminescence signal persists after treatment. This persistence should be further analyzed.